Rancang Bangun Sistem Moitoring Pada Motor Induksi 3 Phase - Den Anjar Nuri Al Hady; ujang wiharja ujang wiharja (Teknik Elektro Universtias Krisnadwipayana, 2026)
In industrial manufacturing, electricity is one of the most critical resources for sustaining operations, particularly production activities. Therefore, electrical systems must remain in optimal condition, ideally operating continuously without interruption. Proper maintenance and periodic monitoring are essential to ensure reliability. Failures in production machinery often arise from multiple factors, not only disturbances in the power supply but also external interferences such as animals.. To address these challenges, a Three-Phase Current and Voltage Monitoring Device was developed to facilitate real-time monitoring of all production panels without requiring direct on-site inspection, thereby improving time efficiency. The system employs a NodeMCU microcontroller integrated with a PZEM-004T sensor, utilizing an IoT-based platform via Blynk. The measurement error achieved is approximately 0.54%. The advantage of this monitoring tool lies in its ability to identify the cause of phase trips when the flowing current exceeds the protection settings, thereby simplifying the analysis of disturbances and enhancing overall system reliability.